2009
DOI: 10.1111/j.1600-0765.2008.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Putative signaling action of amelogenin utilizes the Wnt/β‐catenin pathway

Abstract: Using the TOPGAL transgenic mouse we showed that amelogenin expression in vivo is localized mainly around the root, the periodontal ligament and the alveolar bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 29 publications
4
34
0
Order By: Relevance
“…This result is consistent with a previous report in humans 6) and in 33-day-old mice, in which the same antibody was used 5) . Using the same antibody, we additionally revealed that periodontal ligaments in the developing dental root and dental follicle cells were also immunopositive for amelogenin.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This result is consistent with a previous report in humans 6) and in 33-day-old mice, in which the same antibody was used 5) . Using the same antibody, we additionally revealed that periodontal ligaments in the developing dental root and dental follicle cells were also immunopositive for amelogenin.…”
Section: Discussionsupporting
confidence: 83%
“…Although it was thought that amelogenin expression was limited to the developmental stage and was only present in enamel, recent studies have shown that periodontal tissues also express the protein [4][5][6] . In this study, we showed that periodontal ligaments at 4W were immunopositive for amelogenin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this decade, several studies have revealed that amelogenin isoform genes and proteins are expressed not only in enamel formation but also in adult connective tissue forming cells like rat osteoblasts 6) , rat chondrocytes 6) , odontoblasts 7) , cementoblasts 8,9) and periodontal ligament cells 8,10) . In amelogenin null mice, dramatically reduced expression of bone sialoprotein (BSP), a mineralized tissue-specific marker, was observed at both the gene and protein levels 11) .…”
Section: Introductionmentioning
confidence: 99%
“…Organic matrices including amelogenin in enamel are almost totally removed during mineralization of enamel before a tooth eruption. Ameloblasts generate at least 14 mRNA alternative splicing isoforms of amelogenin, and these amelogenin genes and proteins are expressed in the cells forming connective tissues like osteoblasts (Haze et al, 2007), chondrocytes (Haze et al), odontoblasts (Oida et al, 2002), cementoblasts (Hatakeyama et al, 2003;Nuñez et al, 2010) and periodontal ligament cells (Matsuzawa et al, 2009) in adult tissues.…”
Section: Introductionmentioning
confidence: 99%